2022
DOI: 10.3390/land11101649
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Weighting Methods in Geospatial Flood Risk Assessment: A Trinidad Case Study

Abstract: The Republic of Trinidad and Tobago is an archipelagic Small Island Developing State (SIDS), situated on the southern end of the chain of Caribbean islands. Several factors such as climate, topography, and hydrological characteristics increase its susceptibility and vulnerability to flooding which results in adverse socio-economic impacts. Many Caribbean islands, including Trinidad and Tobago lack a flood risk assessment tool which is essential for a proactive mitigation approach to floods, specifically in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The present study adopted the model validation techniques proposed in the previous studies [83,84]. The flood susceptibility index model in the study region was validated using a receiver operating characteristic (ROC) curve and area under the ROC curve (AUC) for the years 2010, 2021, and 2022.…”
Section: Model Validationmentioning
confidence: 99%
“…The present study adopted the model validation techniques proposed in the previous studies [83,84]. The flood susceptibility index model in the study region was validated using a receiver operating characteristic (ROC) curve and area under the ROC curve (AUC) for the years 2010, 2021, and 2022.…”
Section: Model Validationmentioning
confidence: 99%
“…In the last decade, the intensity and frequency of extremes have increased, where dry seasons are becoming progressively drier, and the rainy seasons have had unfamiliar torrential downpours resulting in both flash and riverine flooding in many Caribbean countries [10].…”
Section: Water Resources Climate Variability and Climate Changementioning
confidence: 99%
“…However, the rapid pace of urbanization in recent years, coupled with the escalating severity of flood disasters, has led to a growing recognition among the public, academia, and governmental bodies that urban drainage and flood prevention systems are influenced by a multitude of factors. Drawing from domestic and international research findings [45][46][47], four primary categories have been identified as influential in the effectiveness of rain-flood regulation: natural, socio-economic, internal, and policy factors. Natural factors, like rainfall and runoff, are essential in determining the magnitude and frequency of flooding, forming the cornerstone of traditional rain-flood management strategies.…”
Section: Urban "Gray-green-blue" Spatial Rain-flood Regulation System...mentioning
confidence: 99%